Mapping Science, Technology, Engineering, and Mathematics (STEM) Research on Physics Topics Using Bibliometric Analysis - Sari, Athiyah Kumala; Ardianto, Didit (Balai Publikasi Indonesia, 2023)
This study aims to provide an overview of physics learning research using the STEM approach in Indonesia. This study uses a descriptive qualitative method which aims to determine the depth of research using a certain matrix so that a conclusion can be presented. This research uses the Publish or Perish application to search for scientific articles. Search for scientific articles indexed by Google Scholar with a publication range between 2018-2022. The results of the search obtained 107 scientific articles that match the search keywords. Furthermore, from 107 scientific articles, a more in-depth screening was carried out so that 45 scientific articles were obtained that specifically discussed STEM Education in physics. The analysis was carried out using the VOS viewer application with the aim of mapping the direction of the research using the keywords